Teacher-Parent Collaboration Management to Improve the Quality of Student Learning - Endi Jamjuri; Helmawati Helmawati (UIN Sunan Gunung Djati Bandung, 2025)
This research is motivated by the importance of teacher-parent collaboration as an integral part of learning quality management in elementary schools. Ideally, such collaboration should be managed in a planned, systematic, and continuous manner. However, empirical observations reveal a gap between the demands for improving learning quality and the actual collaboration practices, which tend to be incidental, lacking formal documentation, and not fully integrated into the school's overall management. This condition was identified at SD Negeri Sukajaya in Cianjur Regency and SD Negeri Legokbedo in Bandung Regency. This study aims to describe and analyze the management of teacher-parent collaboration in enhancing student learning quality through the Plan, Do, Check, and Act (PDCA) cycle. This research employs a qualitative approach with an analytical descriptive method. Data were collected through observation, interviews, and documentation studies involving the school principals, sixth-grade teachers, and parents. Data analysis was conducted through data reduction, data display, and conclusion drawing, with validity tested using triangulation. The results indicate that the collaboration between teachers and parents in both schools has been implemented based on the PDCA cycle, albeit with varying degrees of systematization. This collaboration contributes to the improvement of learning quality, particularly in terms of learning assistance and communication between the school and parents. Nevertheless, strengthening is required in the areas of formal planning, data-driven evaluation, and documented follow-up to ensure that the enhancement of learning quality can proceed optimally and sustainably.